Perilaku Mol Komponen Mineral dan Akuatik dalam Penyimpanan Karbon (Carbon Capture Storage) dengan dan tanpa Sumur Injeksi Air - Lukmana, Allen Haryanto; Kabul Pratiknyo, Avianto; Ragil Putradianto, Ristiyan; Putro Suryotomo, Andiko (Jurnal Migasian, 2024)
This research aims to analyze the changes in mineral and aqueous component moles during Carbon Capture Storage (CCS) with and without water injection in a reservoir field. Using GEM reservoir simulation software, the study models interactions between CO2, reservoir minerals (Anorthite, Calcite, Kaolinite), and aqueous components (Ca++, Al+++, SiO2(aq), HCO3-, CO3--, OH-) over 189 years a time period. The simulation reveals that water injection significantly accelerates mineral dissolution and precipitation, affecting reservoir porosity, permeability, and fluid chemistry. Key findings include enhanced Calcite stability and Kaolinite formation with water injection, alongside noticeable changes in aqueous chemistry. These results provide crucial insights for optimizing water injection strategies in CCS projects and improving reservoir management. The study concludes that water injection enhances mineral stability and impacts ionic concentration in the subsurface environment, aiding in more efficient carbon storage solutions.